A Cost Evaluation of Space Trusses of Large Span - Geiger, David H. (Engineering Journal, 1968)
This study is the first part of a larger economic study dealing with space trusses, domes and cable roofs. The domes and cable roofs considered are characterized by perimeter support around a circular or elliptical plan. This led to the search for a space truss with support at the perimeter. The particular space truss treated in this work met the above requirement. The mechanics of the structural analysis have been discussed elsewhere by Kato, Takashani, Tsushima, and Hirata in a paper presented at the International Conference on Space Structures, and are presented here in summary form. The methods of analysis and design used here are approximate and give rapid preliminary design solutions. As a consequence of this simplification more than a thousand different problems were solved. More difficult than the analysis and design of the truss is the estimating of its cost. In endeavoring to solve this problem the author became indebted to two structural steel fabricators who spent considerable time examining the structural details and supplying him with fabrication and erection costs.